Analisis Implementasi Program Pembinaan Keluarga Sakinah i Kantor Urusan Agama (Studi Kasus Kua Kecamatan Mamajang) - Purwati, Rati; R, Risnah; Fauzan, Ahmad; Sasole, Ismail; Ramli, Muh. Al Faridzi; Farhan, Muh. Fikri; Ishak, Nurfaika (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The purpose of this research is to find out what is behind the importance of fostering a sakinah family in KUA, Mamajang District, Regency and how this coaching is carried out. In this study, the authors used qualitative research methods, by collecting data through observation, interviews and documentation. The informants or subjects in this study were the head of the KUA and an extension agency. The data validity technique used is the triangulation technique, which is the technique of checking the validity of the data by utilizing something from outside the data to check the data. The results obtained from this study are the background of fostering a sakinah family, including as the vanguard of the Ministry of Religion of the Republic of Indonesia, the Office of Religious Affairs (KUA) has a duty and function to carry out some of the tasks of the Office of the City / Regency Ministry of Religion in the field of Islamic Religion Affairs and assist development general government in the field of religion at the District level. And there are also factors that influence the background of developing a sakinah family, namely: Internal factors, the first are overcoming the heavy psychological burdens of fathers and mothers such as pressure (stress) at work, family financial difficulties, and secondly, overcoming conflicts in the family can be overcome, thirdly overcoming egotistical and less democratic attitude, fourthly overcoming the husband/wife’s suspicion that one of them is suspected of having an affair. And there are also external factors, including the first to overcome the interference of third parties in family matters, and the second to overcome the negative association of family members, the third to overcome the wife’s negative habit of gossiping in other people’s homes or at social gatherings and offices, the fourth to overcome the habit of gambling.